2022
DOI: 10.3389/fendo.2022.1078686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the effects of finerenone and SGLT2i on cardiovascular and renal outcomes in patients with type 2 diabetes mellitus: A network meta-analysis

Abstract: BackgroundFinerenone and sodium-glucose cotransporter 2 inhibitors (SGLT2i) have been shown to improve cardiovascular and renal outcomes in patients with type 2 diabetes mellitus (T2DM), while the relative efficacy has not been determined.MethodsThe databases of PubMed, Embase and Cochrane were searched for relevant cardiovascular or renal outcome trials of SGLT2i or finerenone. The end points were major adverse cardiovascular events (MACE), nonfatal stroke (NS), myocardial infarction (MI), hospitalization for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The results from this presented study were in agreement with several studies, which found no significant differences in cardiovascular outcomes between dapagliflozin and empagliflozin. 17 , 18 , 19 , 20 These findings suggested a class of SGLT2 inhibitors in managing cardiovascular risks in DM patients, irrespective of the specific SGLT2 inhibitors used. However, contrasting outcomes have been observed in some studies.…”
Section: Discussionmentioning
confidence: 92%
“…The results from this presented study were in agreement with several studies, which found no significant differences in cardiovascular outcomes between dapagliflozin and empagliflozin. 17 , 18 , 19 , 20 These findings suggested a class of SGLT2 inhibitors in managing cardiovascular risks in DM patients, irrespective of the specific SGLT2 inhibitors used. However, contrasting outcomes have been observed in some studies.…”
Section: Discussionmentioning
confidence: 92%
“…The study selection process is shown in Figure S1. We identified a total of 1483 records, and 25 reports were included in the final analysis. , Two publications were from the same original study and their data were pooled. , Thus, 24 studies, including 15 RCTs and 9 observational studies, were included. These studies were published between 2019 and 2023 and enrolled a total of 12,413 patients (6175 in the SGLT2i group and 6238 in the non-SGLT2i group).…”
Section: Resultsmentioning
confidence: 99%
“…It can be combined with finerenone and may achieve the superposition of cardiorenal benefits effect via mechanism complementarity. The mechanism of action of SGL2i may be related to the hemodynamic effects and the decrease of albuminuria, and the kidney single-cell transcriptome data showed that SGLT2i affected mitochondrial function in proximal tubular cells [33,34]. Furthermore, SGLT2i has been shown to normalize systolic blood pressure and mitigate the development of tubular fibrosis in mice [35].…”
Section: Discussionmentioning
confidence: 99%